THE UNITY OF ESSAY WRITTEN BY STUDENTS OF ENGLISH EDUCATION PROGRAM AT UNIVERSITY OF PGRI ADI BUANA SU RABAYA THROUGH “PADA ZAMAN DAHULU” STORY - Rikat Eka Prastyawan (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2017)
Essay is a piece of paper at least three paragraph longs involving introductoryparagraph, body, and concluding paragraph. It could be developed from the paragraph. However, students often get difficulties to find what they must write in their paper. Knowing that condition, the way how to get ideas could be achieved by watching film. The story ―Pada Zaman Dahulu‖ broadcasted in MNCTV could be used to keep the students‘ ideas while writing. In that story,there is a genceric structure which the students could develop in writing Essay. Therefore, in this study, the researcher stated the research question: How is the unity of Essay written by the students of English Education Program through the story ―Pada zaman Dahulu‖. This study aims to describe how unity the students‘ essays are. The researcher uses a qualitative design to describe the data which be collected by using purposive random sampling. After doing data collection technique, the researcher analyzes the students‘ essay which got A score in their essay by using the theory of Essau unity stated by Zemach (2005:78). Result shows that the students‘ Essays have good unity that could be reflected from the ideas connections each others. All the ideas written by the students were connected to the thesis statement and the supporting ideas in the main body have connections with the topic sentence. So, it could be concluded that the story ―Pada Zaman Dahulu‖ could keep the students‘ ideas while writing an Essay. So, the students‘ ability in creating an essay depends on the way how they gather the ideas to arrange in a proper components of Essay